Effect of Diluent on the Rheological and Mechanical Properties of Epoxy-Carbon Nanotubes Composite. (April 2019) - Oo, T. T.; Abdullah, A.H.; Anwar, M.; Khandoker, N. A. N.; Islam, S.; Debnath, S.
Abstract: The incorporation of carbon nanotubes (CNTs) with polymer material has been the focus of research for many years, due to relatively simple processing procedure and high potential application. However, it is found to be difficult to get very good CNT dispersion, due to the viscosity built-up during the CNTs dispersions. This project investigated the effect of viscosity of the polymer resin through rheological and mechanical characterization. The key ingredient applied for the modification of the epoxy-CNTs viscosity properties is the ethanol diluent. The effect of ethanol diluent on epoxy-CNTs composites was studied through addition of 5% and 10% weight ratio of ethanol to the epoxy-CNTs suspension with increasing CNTs content up to 0.5% weight proportion. The produced specimens were studied and compared with non-diluent specimens through viscometer, optical microscope and tensile strength testing. The addition of ethanol was found to reduce the viscosity of epoxy-CNTs composite through shear-thinning behaviour, in which results due to a high shear rate condition and was found to be beneficial in reducing the CNTs agglomerations and clusters formation within the composite structure. Moreover, improvement in tensile strength of epoxy-CNTs suspension with diluent was observed over non-diluent epoxy-CNTs specimens. The highest gain in tensile strength among the epoxy-CNTs sample was the one containing 0.5% CNTs and 5% ethanol weight ratio, the highest CNTs content tested in this experiment. The experimental results proved that ethanol diluent is beneficial to epoxy-CNTs composites in reducing agglomeration, improving flow-ability and tensile strength.